Solution of the cosmological constant problem within holographic cosmology - Nastase, Horatiu [UNESP] (Elsevier, 2020)
Within the holographic cosmology paradigm, specifically the model of McFadden and Skenderis, but more generally than that, the cosmological constant is found to naturally flow from a large value, to a small value, which can even be as low as the needed ∼10−120 times the original, along with the dual RG flow. Within this context then, the cosmological constant problem is mapped to a simple quantum field theory property, even though the exact mechanism for it in gravity is still obscure. I consider several examples of gravity duals to explain the mechanism.